2022
DOI: 10.1111/jmg.12701
|View full text |Cite
|
Sign up to set email alerts
|

Repeated metamorphism in the pelitic granulites of the Hidaka metamorphic belt, Hokkaido, Japan: Implications for the formation of the present‐day trench‐arc‐basin system in NE Asia

Abstract: The timing and mechanism of the tectonic transition from an active continental margin to a trench‐arc‐basin system in NE Asia are debated. In this study, we report the pressure–temperature–time (P–T–t) path of this transition based on petrographic observations, phase‐equilibrium modelling, and U–Pb ages of zircon and rutile from pelitic granulites in the Hidaka metamorphic belt (Hokkaido, Japan). The granulites contain an early phase mineral assemblage of staurolite + sillimanite + biotite + plagioclase + quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Recent investigations, including heat flow calculations, analysis of geomagnetic anomalies, and the study of granulite‐facies metamorphism from Hokkaido, Japan, have strongly suggested that the opening of the Japan Sea occurred approximately at 20 Ma (e.g., Lallemand & Jolivet, 1986; J. Zhang et al., 2022). The mechanism responsible for the Japan Sea opening is believed to result from the joint slab rollback of the PP and trench rollback (Xu et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations, including heat flow calculations, analysis of geomagnetic anomalies, and the study of granulite‐facies metamorphism from Hokkaido, Japan, have strongly suggested that the opening of the Japan Sea occurred approximately at 20 Ma (e.g., Lallemand & Jolivet, 1986; J. Zhang et al., 2022). The mechanism responsible for the Japan Sea opening is believed to result from the joint slab rollback of the PP and trench rollback (Xu et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…From the Miocene, continuous slab roll‐back of the Pacific Ocean and retreat of the trench (Xu et al., 2022) triggered extensive back‐arc extension on the NE Asian continental margin (Xu et al., 2022) which caused the opening of the Sea of Japan (ca. 24–19 Ma, Tang et al., 2016; J. Zhang et al., 2022), exhumation on the NE Asian continental margin (ca. 23 Ma, Y. P. Zhang et al., 2022) and the GXR (ca.…”
Section: Discussionmentioning
confidence: 99%